Use of agro-industrial wastes as substrates for Î±-amylase production by endophytic fungi isolated from Piper hispidum Sw - Orlandelli, Ravely Casarotti; Santos, Mariana Sanches; Polonio, Julio Cesar; Azevedo, João Lúcio; Pamphile, João Alencar (Acta Scientiarum. Technology, 2017)
Millions of tons of corn, pineapple, sugarcane and wheat are annually produced and their industrial processing generates large amounts of wastes. Current study evaluated the use of corncob (CC), pineapple peel (PP), sugarcane bagasse (SB) and wheat bran (WB) as substrates for α-amylase production by submerged cultures of nine endophytes from Piper hispidum Sw. Initially, fungi were grown on a starch medium and the cup plate assay showed that five strains were amylase-positive: Bipolaris sp. JF767001, Marasmius cladophyllus JF767003, Phlebia sp. JF766997, Phyllosticta capitalensis JF766988 and Schizophyllum commune JF766994, with enzymatic halos ranging between 6.30 ± 0.08 and 8.87 ± 0.68 mm in diameter. Further, the use of agro-industrial wastes was evaluated by the cup plate assay, where the highest halo diameters were obtained from fungi grown on PP or SB: up to 15.00 ± 0.16 mm (Phlebia sp.) and 14.80 ± 0.18 mm (S. commune), respectively. Submerged cultures with PP or SB showed the highest levels of α-amylase activity according to the starch-iodine assay, or rather, up to 4.14 ± 0.02 U mL-1 (Bipolaris sp.) and 4.09 ± 0.02 U mL-1 (Phlebia sp.), respectively. Results give an in-depth knowledge on tropical endophytes that might be α-amylase sources, and indicate the suitability of these agro-industrial wastes as substrates for fungal enzymatic production.